KEPEMIMPINAN DAN KOMPETENSI PENGARUHNYA TERHADAP PENGEMBANGAN KARIR DAN IMPLIKASINYA PADA KINERJA APARATUR DI KOTA PALEMBANG - Marzuki Alie (Universitas Indo Global Mandiri)
Leadership, Competence influence on Career Development and Its Implications on Performance Apparatus Palembang, coordinator of the research institute under the University of inclusive do Global Mandiri Palembang (Economic Studies Graduate Program Management) This study aims to assess the Influence of Leadership, Competence influence on Career Development and Its Implications on Performance Apparatus in Palembang. The study was conducted during the four months of the Apparatus in Palembang City Government Secretariat, with a population of 100 Apparatus to test the questionnaire conducted. Research data analysis using descriptive and inferential statistical methods. Model analysis using Structural Equation Model (SEM) with the composition of the sub-structure: Leadership and Competence as exogenous and Career Development and Performance as endogenous variables. Results showed (1) in the sub-structure of the first bahwaKompetensi and Leadership jointly positive and significant impact on Career Development, but only partially leadership has positive effects dansignifikan (2) on the main structure that leadership, competence and Career Development jointly-Same or partially positive and significant impact on performance in Palembang.From the analysis of the influence of the direct or indirect can be concluded that in order to improve performance in Palembang variable competence has a direct effect is more dominant than the through variable performance (0,12), otherwise variable leadership (0,07).Disarankan To the Mayor of Palembang in Palembang, that in order to improve the performance both need attention focused on efforts to improve the system of Career Development Apparatus and competence necessary to increase the attention focused on efforts to increase the role of leadership, especially in applying participatory management in planning and decision-making.Keywords : Leadership,Competence,Career Developmen, and Performance, Apparatus